Grundtvigs møde med Irenæus - Thaning, Kaj (Grundtvig-studier, 1953)
Grundlvig's Encounter with lrenæus - his way towards "Dagningen" ("Daybreak") and "De levendes Land " ("The land of the living").By Kaj Thaning. Among the periods of greatest tension in Grundtvigs carear as a clergyman were the years 1823-24; his sermons which have been preserved from this period bear witness, Sunday after Sunday, to a series of new advances in understanding , which are primarely due to his encounter with Irenæus, one of the Fathers of the Church , whose work "Against Heretics" accidentally came into his hands, perhaps as early as the end of 1822. Grundtvig had been subjected to influences from two very different directions, from the Lutheran Chistianity of repentance of his home, to which he "went home" after the erisis of 1810, and from Romanticism, which had brought him face to face with "the mystery of man" during his period as at tutor on Langeland. It became plain during the years after 1810 (including the theological period up to 1815) that Lutheranism had not solved for him the questions which had been stirred to life on Langeland and in Copenhagen. Nor did the foliowing period (1816-21) bring him clarity. In this period - freed from the obligations of his ordi nation-oath - he sought to work out the questions raised by Romanticism , especially in the periodical "Danne-Virke" . lt was light on the nature of man that he sought. Here Lutheranism failed him. lt and the Bible threw light on the way to salvation, but not on man's life as man nor on the life of nations.But when Grundtvig became a parish clergyman again, no further postponement was possible. Each Sunday the battie had to be joined, the truth had to be proclaimed. But Grundtvig wa s not clear in his own mind. His sermons reflect a struggle - sometimes desperate - with the sacred text, with the unbilief of the period - and with his own Jack of clarity. But at the same time that the influence of his reading of Irenæus begins to manifest itself, something new emerges in his sermons. The clari Heation which is taking place leads first to that "enlivening" in Advent, 1823, to which Grundtvig himself refers in "Nyaars-Morgen", and then to the poem, "0 dejlige Land", the composition of which undoubtedly took place between the sermons Feb. 1st and Feb. 8th, 1824, six months earlier than has been generally assumed. (It is usually dated after "Nyaars-Morgen", in the summer of 1824.) Grundtvig's enconter with Irenæus was of such great significance that it changed his conception of Christianity and thereby also helped to change the aspect of Church life in Denmark. Through it he was brought into confaet with ideas of the Early Church that were apart from and in con Hiet with "the pilgrims way of thought" which was something essential in the Lutheran Christianity of repentance which it had been Grundtvig's aim to revive.The first and decisive contribution of the ideas of Irenæus to Grundtvig sermens is a new conception of man created in the image of God. In the middle of the Lenten season, the period in the Church's year when the Lutheran Chri stianity of repentance reveals itself most charicteristically, Grundtvig - in a prolongation of his "Danne-Virke" period - begins to proclaim "the sound and true knowledge of man," the knowledge of "what man is in ourselves and in others, what man can do of himself, whither he is impelled , and what he stands in need of in order to complete his life with gladness." Without such a knowledge of man all knowledge of God is wasted upon us, and the year ning for a Saviour will remain (as in Lutheranism) weak and faint. Therefore light must be shed upon "everything human." This is the programme which is later carried farther in his line of poetry: "First the man and then the Christian ."However, on first acquaintance this new discovery alarms Grundtvig - and Lenten Christitianity comes back into the centre of the picture. But the new thought slowly works its way to the front. And it is clear that it is lre næu s who inspired the sermon already mentioned, when Grundtvig, some time after Easter, sheds "new light upon man" through the idea of the Early Church, which is new to him, that the Fall was due to seduction, overhastiness, the wiles of the Devil. The natura! man is not the friend of sin, but its slave. In spite of the Fall, there are in him fragments of God's image.Irenæus, in his conllict with the Gnosticism which denied reality , pointed to God's work of creation , to the first Adam as the object of God's healing work by means of the second Adam, in Whom the creation is "taken up" ("recapitulated"). This becomes a fundamental thought in Grundtvigs con ception of Christianity. But, curiously enough, he does not recognise his debt to Irenæus on this point . And it is only after 1832 that Grundtvig joins issue directly on this basis against Lutheranism , against the denial of man, of the work of creation, by Pietism and orthodoxy. Until then it is rationalism which is the chief enemy, the "Gnosticism" in the modern period.Irenæus now bring s about a revival of the ideas derived by Grundtvig from Romanticism . Grundtvig's problem was the relation between them and Lutheranism. Here Irenæus become s the mediator, since his emphasis on the natura! man comes to signif y for Grundtvig a kind of justification of the longings and vital impulses of his own youth, which he now understands as having been created by God Himself . Irenæu s gains authority for him through the position he occupies in the oral tradition going back to St. John. The Apostle's preaching of love is now also cernbined in Grundtvig's sermons with fhe Ro mantic conception of love as the eternal fire which shines behind everything. He preaches about its essence and "eternal nature ". Lutheranismand the Ro mantic poet now seek in fellowship to shape the sermon . From this first hornage to love a line -not straight, but winding - leads onward to "0 dejlige Land".Undoubtedly a new inspiration now comes upon the scene as well, namely Steff ens' "Of False Theology and the True Faith". At all events Grundtvig's conception of the Church now begins to develop. It may have its root in the oral tradition, to which Irenæus had opened his eyes, and which justified for him the new conception of the nature of man. But it was Steffens who directed his attention to the concrete "Church community", the union of "learned and laymen ", just as he sat before him the task of formulating unity in the faith. When Irenæus later helps him to solve the problem (the Apostolic Creed), he f orgets on account of this what he owes to Irenæus in the first instance.Light upon man as created by God now leads on to a remarkable sermon in which Denmark is pictured as a symbolic likeness of the Church - thus forshadowing "Nyaars-Morgen". But perhaps through this very concrete image the way is also prepared the poem on "De levendes Land", which really grows forth from his constantly increasing emphasis on the work of creation. Through two more very signif icant sermons on the operation of the Holy Spirit (showing the influence of Steffens?) and on the hope of immortality one is led to understand the new advance signi Hed by the sermon on "Dagningen" on the first Sunday in Advent. In itself it merely says that enlightenment is the work of the Holy Spirit, but from the foregoing sermons we can clearly see what it is that Grundtvig feels himself to be "enlightened" about: the "limitless longing for life" of his youth is emplanted in him by God, Who will cause the hope of immortallity to grow and will nourish it with the sym bols of the Bible, such that fallen man is led "back" to Paradise, and thereby forward to the new Jerusalem. This is the conception of lrenæus, which also leads forward to the poem on "De levendes Land".The theme of growth is transferred to the seasons of life, to "all the visible creation". and in referring to spring "in the midst of the world 's winter" Grundtvig takes another step forward toward s the poem, in the attitude he adopts towards Kingo's "Far Verden, far vel", to whose renunciation of life his own "longing for life" is opposed. And, confronted with the text about love as the fulfilment of the law (4th- Sunday aftcr Epiphany) he preaches the sermon that leads on to the poem which finds "the land of the living" through the love that links Heaven and earth. Even if it is only the later hymn ("0 Kristelighed") which fully carries through the Christian conception that etemallife with "the joy of the living" is a reality now, still the poem repre sents a break with Kingo. But it is still to some extent the ideas of Roman ticism which he uses against Kingo. It is not till 1832 that Grundtvig makes a seperation between the Christian faith and the Romanticism which in 1823-24 became combined with his Lutheranism - curiously enough, as a result of his encounter with lrenæus!